Inpatient health care utilization in the United States among children, adolescents, and young adults with nephrotic syndrome - Gipson, Debbie S; Messer, Kassandra L; Tran, Cheryl L; Herreshoff, Emily G; Samuel, Joyce P; Massengill, Susan F; Song, Peter; Selewski, David T (American journal of kidney diseases, 2013)
Data describing inpatient health care utilization in children with nephrotic syndrome and related severe complications are limited. Our goals were to describe the charges, length of stay (LOS), and number of hospitalizations among children, adolescents, and young adults with nephrotic syndrome. A cross-sectional analysis of the Kids' Inpatient Database (KID) database from the Healthcare Cost and Utilization Project (HCUP). The HCUP-KID is an all-payer database of hospital discharges for children, adolescents, and young adults in the United States compiled every 3 years by the Agency for Healthcare Research and Quality. HCUP-KID data were obtained for the 2006 and 2009 cohort years. We identified patients by searching discharges for nephrotic syndrome International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis codes. Patient demographics, disease complications in children, adolescents, and young adults hospitalized with nephrotic syndrome. Number of hospitalizations, mean charges, and LOS for children, adolescents, and young adults hospitalized with nephrotic syndrome. There were 6,308 hospitalization discharges in children, adolescents, and young adults with a primary or secondary diagnosis of nephrotic syndrome reported by 38 and 44 states in 2006 and 2009, respectively, representing an estimated 9,934 discharges nationally. Nephrotic syndrome resulted in an estimated 48,700 inpatient days and charges totaling $259 million. The mean charge per hospitalization was ∼$26,500 (SE, $1,100) and LOS was 5 days (SE, 0.1). 16% of discharges for nephrotic syndrome had a diagnosis code for at least one severe complication, including thromboembolism (3.6%), septicemia (3.8%), peritonitis (2.6%), pneumonia (5.4%), or diabetes (2.4%). Multivariable analysis showed age 15 years or older, race, higher socioeconomic status, acute renal failure, thromboembolic disease, hypertension, and infections predicted higher mean hospitalization charges. The HCUP-KID database collects data on a hospitalization level. Consequently, health care utilization on an individual patient level or in the outpatient environment is not possible. We present a comprehensive description of inpatient health care utilization in children, adolescents, and young adults with nephrotic syndrome. The complications of nephrotic syndrome, including thromboembolism, infection, and hypertension, contribute significantly to these charges.